Factors influencing decision to seek health care: a qualitative study among labour-migrants' wives in northern Tajikistan - Jamila Nabieva; Aurélia Souares (BMC, 2019)
Abstract Background This qualitative study aimed to investigate the health seeking behaviour of rural women in northern Tajikistan, with specific focus on antenatal and obstetric complications as a result of delayed access to health services. Due to the unprecedented level of labour migration among men in the border region of Tajikistan, Isfara, the study specifically focused on migrants' wives residing with their in-laws. Methods Using an adapted "Three delays" model which suggests three major causes of delayed access to maternity services - decision to seek care , reaching a healthcare facility and receiving necessary care - we conducted 29 in-depth interviews with labour migrants' wives, 16 semi-structured interviews with healthcare service providers and 2 focus-group discussions with 16 mothers-in-law in Isfara district. Results Our study demonstrated that the most crucial and conditioned factor of access to maternity services for labour migrants' wives is a decision to seek care. While reaching a healthcare facility (geographical accessibility, time and transportation costs) and receiving necessary care (availability of services, financial affordability and perceived quality of care) were rarely reported as obstacles towards timely access to maternity services, decision to seek care was found to be an intricate interplay of several factors: traditional gender and family roles (particularly in the absence of the husband), the age of the mother-in-law, cultural beliefs and perceptions about pregnancy and maternity, and widely spread myths about certain health conditions and services. Conclusions Our study concludes that the traditional pattern of seeking health care among women in northern Tajikistan may often cause delays in accessing necessary maternity services and result in adverse health outcomes for women. We suggest that effective strategies to reduce maternal morbidity and mortality in rural Tajikistan should, along with strengthening healthcare structures, embark on community education and awareness raising with special focus on mothers-in-law and other traditional decision-makers in households.